Tinjauan Kritis Penerapan Syarat Kesahihan Hadis dalam Skripsi Prodi Ilmu Hadis UIN Jakarta 2024 - Ananda Nurul Hasanah; Hilmy Firdausy (Prophetica: Journal of Hadith Studies, 2025)
This study evaluates the application of hadith authenticity criteria (ṣiḥḥat al-ḥadīth) in undergraduate theses produced by students of the Hadith Sciences Study Program at UIN Syarif Hidayatullah Jakarta in 2024. Using a qualitative descriptive-analytical approach and content analysis of 36 theses that specifically address hadith quality, the study finds that only 4 (11.11%) successfully apply all five conditions of a ṣaḥīḥ hadith: continuity of the isnād (ittiṣāl al-sanad), moral uprightness (ʿadālah) and precision (ḍabṭ) of narrators, and freedom from irregularity (shādhdh) and hidden defects (ʿillah). The remaining 88.89% demonstrate significant methodological deficiencies, particularly in their treatment of matan criticism and the analytical application of al-jarḥ wa al-taʿdīl. These findings reveal a persistent gap between theoretical instruction and practical implementation in the academic writing of Islamic higher education students, pointing to systemic weaknesses in academic supervision, curriculum design, and the uncritical use of digital hadith resources. The article argues for structural reforms in hadith pedagogy within Indonesian Islamic higher education.